Pengaruh Kualitas Produk terhadap Minat Beli Ulang yang Dimediasi oleh Kepuasan Pelanggan pada Produk Minuman Penambah Tenaga non Cair Extra Joss pada Mahasiswa program studi Manajemen - Ahmad, Kherulyadi; Hafidh Nurmansyah, Abdul Ahmad (IPM2KPE, 2024)
This study aims to determine the effect of product quality on repurchase intention mediated by customer satisfaction on non-liquid energy drink product extra joss, especially for students of management study program. The research instrument used has passed validity and reliability tests. This data collection tool is used to interview respondents aged 16-40 years who have experience consuming extra joss products. A total of 119 respondents participated in this study. The data collection method used is cross-sectional or one shot study. Data analysis was carried out using a quantitative descriptive approach, normality test, simple regression, multiple linear regression using SPSS version 24 software, and the use of the sobel test. Of the four hypotheses proposed, two of them are supported by empirical findings. The results of this study indicate that product quality has a direct effect on repurchase intention mediated by customer satisfaction. Meanwhile, other concepts that can directly influence repurchase intention can be explained by future research. The implications of these findings provide benefits for the company or product manager being evaluated, namely Extra Joss, and similar industries, related to designing relevant strategies to improve the quality of these attributes. Keywords: Product Quality, Customer Satisfaction, Repurchase Interest